Perubahan Morfologi dan Pertumbuhan Handeuleum (Graptophyllum pictum L. Griff) akibat Iradiasi Sinar Gamma - Rosmala, Arrin; Khumaida, Nurul; Sukma, Dewi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2015)
ABSTRACTHandeuleum (Graptophyllum pictum L.Griff) is a medicinal plant widely used as a traditional medicine due to its benefecial content. Therefore, it should be developed as one of the leading Indonesian medicinal plants. The purpose of this research was to study the effect of gamma ray irradiation on morphological alteration and growth of Handeuleum accession from Bogor. The doses of gamma rays were 0, 15, 30, 45, 60, 75, 90, and 105 Gy. The results of the research showed that gamma-ray irradiation induced morphological changes and influences the growth of Handeuleum. Irradiation dose at rate of 105 Gy produced new leaf morphology in Handeuleum, namely cordate. Doses of 60, 75, 90, and 105 Gy produce stunted plants with stiff and yellowish-green leaves. The dose of 45 Gy produced relative green color index which was higher than the control plants.Keywords: handeuleum, gamma irradiations